Trueperella pyogenes promotes the synthesis and maturation of IL-1β in murine macrophages - Yang, Meimei; Hu, Yunhao; Wang, Junwei; Zhang, Wenlong; Liu, Bin (Frontiers in Immunology, 2025)
Trueperella pyogenes (T. pyogenes) is an important opportunistic pathogen in animals and can also cause diseases in humans. Previous studies have shown that T. pyogenes infection can upregulate the levels of pro-inflammatory cytokines, such as interleukin-1 beta (IL-1β), in host tissues. However, the underlying mechanisms are not yet fully understood. In the current study, we found that both inactivated T. pyogenes cells (iTP) and pyolysin (PLO, a major virulence factor of T. pyogenes) can promote the transcription of the IL-1β gene both in vivo and in vitro. iTP-caused upregulation of IL-1β gene transcription is dependent on nuclear factor-kappa B (NF-κB). On the other hand, we determined that PLO, but not iTP, can promote the maturation of IL-1β by activating caspase-1-mediated processing of pro-IL-1β. Further, we confirmed that PLO can induce potassium ion (K+) efflux in mouse macrophages, thereby activating caspase-1 in a Nod-like receptor protein 3 (NLRP3)-dependent manner. Blocking K+ efflux or knocking down the expression of NLRP3 both inhibited caspase-1 activation and pro-IL-1β processing. Taken together, these findings demonstrate that T. pyogenes can promote IL-1β expression at both the transcriptional and post-translational levels in a murine macrophage model. These results significantly enhance our understanding of the pathogenesis of T. pyogenes and the interactions between T. pyogenes and host immune system.